2005
DOI: 10.1056/nejmoa042982
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ulcerative Colitis with a Humanized Antibody to the α4β7Integrin

Abstract: In this short-term study, MLN02 was more effective than placebo for the induction of clinical and endoscopic remission in patients with active ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
477
0
13

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 661 publications
(501 citation statements)
references
References 29 publications
11
477
0
13
Order By: Relevance
“…24 Targeting a4b7 integrin will likely not put patients at risk for this serious complication, as immunologic protection of the central nervous system should remain intact given the specificity of a4b7 integrin for intestinal tissue. A specific MoAb (vedolizumab) has already been developed against a4b7 integrin and is being used in ongoing clinical trials for the treatment of inflammatory bowel disease, 25 and we plan to test this approach for the treatment of intestinal GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…24 Targeting a4b7 integrin will likely not put patients at risk for this serious complication, as immunologic protection of the central nervous system should remain intact given the specificity of a4b7 integrin for intestinal tissue. A specific MoAb (vedolizumab) has already been developed against a4b7 integrin and is being used in ongoing clinical trials for the treatment of inflammatory bowel disease, 25 and we plan to test this approach for the treatment of intestinal GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…The easiest approach to developing a selective antagonist is with complex-specific monoclonal antibodies. A complex-specific α 4 β 7 antibody MLN-02 has shown efficacy in a Phase II trial for ulcerative colitis 157 and specific small-molecule antagonists for α 4 β 7 have been discovered 156 .…”
Section: Role Of Integrin Cytoplasmic Tailsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] All 20 studies reported a mean age. The composite mean age was 39.2 years with a mean range of 36.2 to 44 years.…”
Section: Biological Agentsmentioning
confidence: 99%